2020
DOI: 10.1093/jas/skaa280
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal milk protein genotypes with preweaning calf growth traits in beef cattle

Abstract: The objectives of this study were to investigate milk casein polymorphisms in dams, and to determine the impacts of maternal casein genotypes on growth traits of their sucking calves. Milk samples from 433 dams of the breeds German Angus (GA) and German Simmental (GS) were typed at the milk protein loci αs1-casein (αs1-CN), β-casein (βCN), αs2casein (αs2-CN) and κcasein (κ-CN) via isoelectric focusing. Associations between casein genotypes in maternal milk with growth traits of their 1,872 calves were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Braunschweig et al [30] compared the parental haplotypes B-B-A-A and B-B-A-B for CSN1S1-CSN2-CSN1S2-CSN3 in Swiss Brown Cattle and associated B-B-A-A with lower casein content and higher whey protein content in daughter milk. Similarly, the maternal composite casein genotype CSN1S1 BB -CSN2 A2A2 -CSN1S2 AA -CSN3 AB have been recently associated with pre-weaning offspring growth in German cattle [23].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Braunschweig et al [30] compared the parental haplotypes B-B-A-A and B-B-A-B for CSN1S1-CSN2-CSN1S2-CSN3 in Swiss Brown Cattle and associated B-B-A-A with lower casein content and higher whey protein content in daughter milk. Similarly, the maternal composite casein genotype CSN1S1 BB -CSN2 A2A2 -CSN1S2 AA -CSN3 AB have been recently associated with pre-weaning offspring growth in German cattle [23].…”
Section: Introductionmentioning
confidence: 94%
“…Several investigations on cattle breeds in other countries associated milk protein variants with milk yield, composition and coagulation traits [20][21][22]. For instance, the β-CN A2 , predominant in zebu cattle presented positive effects on calf growth [23]. This variant is also of high interest for human health because of its ability to promote better digestion efficiency and antibacterial activity [14,17,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barendse et al (2007) studies on the Angus breed revealed that the G/G genotype of the bRORC gene encoding the retinoic acid receptor has a positive effect on marbling. Hohmann et al (2020) studied the milk casein genes polymorphism in Angus breed females of the German population and determined the maternal casein genotypes influence on their calves' growth characteristics. It was found that calves from females with the K-CN BB and α s1-CN BB genotypes had higher indicators of average daily growth and live weight at weaning.…”
Section: Introductionmentioning
confidence: 99%